2021
DOI: 10.1155/2021/5177313
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Inlet Guide Vanes on the Performance of Shaft Tubular Pumps

Abstract: To study the influence of inlet guide vanes (IGVs) on the pressure pulsation of a shaft tubular pump, this paper first conducts an experiment to study IGVs. Then, numerical calculations of the shaft tubular pump with and without IGVs are performed to analyze the hydraulic performance and pressure fluctuation characteristics. Finally, the reliability and accuracy of the data are verified by a model test. Numerical simulation results show that with additional IGVs, the pressure pulsation amplitude at the impelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Their research revealed that the hydraulic efficiency of the pump device is largely determined by the characteristics of the outlet channel. Jiao, H. [18] studied the influence of front guide vanes on the pressure pulsation of the shaft tubular pumping device and discovered that the front guide vane may enhance the water inlet condition of the impeller and decrease pressure fluctuations on the blade surface. Xu, L. [19] studied the energy characteristics of the front shaft-type tubular pumping station at the inlet angles of two guide vanes, with the aim of increasing the pump station's efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Their research revealed that the hydraulic efficiency of the pump device is largely determined by the characteristics of the outlet channel. Jiao, H. [18] studied the influence of front guide vanes on the pressure pulsation of the shaft tubular pumping device and discovered that the front guide vane may enhance the water inlet condition of the impeller and decrease pressure fluctuations on the blade surface. Xu, L. [19] studied the energy characteristics of the front shaft-type tubular pumping station at the inlet angles of two guide vanes, with the aim of increasing the pump station's efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on shaft tubular pump devices has focused on the structural design optimization of the pipes [17,18], the influence of the position and shape of the impact of the impeller and guide vane on energy performance [19][20][21][22][23], and the flow field and internal flow properties of the devices [24]. However, studies on the tip clearance of the impeller of a shaft-tubular pump device are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a free surface vortex tends to trigger low-frequency PP and induce unit resonance. Jiao et al [14] found that the installation of the inlet guide vane at the impeller inlet of a shaft tubular pump could induce low-frequency PP. Yang et al [15] studied the PP characteristics in the axial-flow-pump skip-shaped channel by using numerical simulation.…”
Section: Introductionmentioning
confidence: 99%